Estado y religión: tendencias conceptuales incidentes en la apreciación pública del fenómeno religioso - Jorge Del Picó Rubio (Revista de Estudios Sociales, 2018)
Based on the renewed interest in the public impact of religious practices, this article spotlights and analyzes some significant contemporary trends in the way they are seen in the public sphere which affect their legal recognition by legal systems in the West. Our analysis mainly focuses on a review of current doctrines in this area, whose influence is widely acknowledged in Latin America, and it is undertaken from a socio-legal standpoint. Among other aspects, it addresses the dominant trends in the institutional approach to religious practices, the leading role they have again assumed in the public sphere, their political-legal recognition, the place which communities of worshippers hold in secular systems, the overriding importance in legal systems of the principle of religious freedom and the status of religion in a laical State.